1978
DOI: 10.1002/ange.19780900115
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung von cyclo‐Heptaschwefel, S7, aus S8

Abstract: Angew. Chem. Int. Ed. Engl. 15,442 (1976); diedort beschriebenen Reaktionen sind Einquantenprozesse, da eine lineare (nicht quadratische) Intensitatsabhangigkeit besteht.E. P ! Dehn~low~, Tetrahedron Lett. 1969, 4283; dort weitere Hinweise.G. Kaupp, Angew. Chem. sowie Angew. Chem. Int. Ed. Engl., im Druck.( 2 ) ist starr und hat im mittleren Ring eine sterisch belastete Bindung in fi-Stellung zur Doppelbindung. Photolyse (253.7 nm) bei 83 K fuhrt LU einer weinroten, sehr lichtempfindlichen (546nm) Verbindung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…With respect to our previous force field calculations 15 in which seven force constants were considered, f r , f R , f rR , rf r˛, Rf R˛, rRf˛and r 2 f , an additional interaction constant f˛˛was considered here. Its value and that of the f constant were derived from the S 8 force field 25 (Table 5). For the sake of simplicity, the interaction constants f rr , rf r , Rf R and rRf˛ were disregarded, their numerical values being weak 26 (e.g.…”
Section: Valence Force Field Calculationsmentioning
confidence: 99%
“…With respect to our previous force field calculations 15 in which seven force constants were considered, f r , f R , f rR , rf r˛, Rf R˛, rRf˛and r 2 f , an additional interaction constant f˛˛was considered here. Its value and that of the f constant were derived from the S 8 force field 25 (Table 5). For the sake of simplicity, the interaction constants f rr , rf r , Rf R and rRf˛ were disregarded, their numerical values being weak 26 (e.g.…”
Section: Valence Force Field Calculationsmentioning
confidence: 99%
“…A detailed analysis of extensive pressure measurements of saturated sulfur vapor showed S7 to be one of the major components of this complex mixture with S7 concentrations ranging from 12 mol-% at 200 °C to 26% at 400 °C [6,11]. Later it was discovered by IR and Raman spectroscopy that liquid sulfur after equilibration, besides Ss, contains the cyclic molecules Sö, S7, and S12 [12] as well as larger rings [13], and pure S7 could be obtained from the quenched melt by CS2 and toluene extraction [14], Recent investigations have further shown that S7 is one of those ubiquitous molecules produced in many reactions but discovered only recently by means of molecular spectroscopy. Such reactions are, for example, the irradiation of Se, Ss, and S10 in CS2, CH2Cl2 or toluene solutions [15], the acid decomposition of aqueous sodium thiosulfate [16], and the thermal decomposition of sulfur diiodide at 25 °C [17].…”
Section: Introductionmentioning
confidence: 98%
“…10 Comparison of the ratios xi/xs obtained through Rau's model [59] (i = 7 full line, i = 6 dotted line), and Xi/XS calculated from Raman spectroscopy data (i = 7: -. -, i = 6: -*-)for saturated sulfur [58]. Assuming Rau's S7 entropy of 407.6 J mol:" K -I to be correct [25], the reaction entropy for the equilibrium amounts to~S29g = 37.3 J mol--1 K -I while Rau et al arrived at a value of 31.4 J mol-I K-1 [5].…”
Section: Vapor Composition and Thermodynamicsmentioning
confidence: 99%
“…8 Considering that the thermodynamic properties of cyclic Ss are well established [5,58], it seems more appropriate to relate the behavior of the two other more abundant species to that of Ss. We have therefore compared in Fig.9 the xJxs ratios calculated from Rau's model [59] with the values obtained from the observed ratios IUI~.…”
Section: Vapor Composition and Thermodynamicsmentioning
confidence: 99%